Aspergillus derived mycotoxins in food and the environment: prevalence, detection, and toxicity - Navale, Vishwambar; Vamkudoth, Koteswara Rao; Ajmera, Shanthipriya; Dhuri, Vaibhavi (Toxicology Reports, 2021)
<em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Aspergillus<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> species are the paramount ubiquitous fungi that contaminate various food substrates and produce biochemicals known as mycotoxins. Aflatoxins (AFTs), ochratoxin A (OTA), patulin (PAT), citrinin (CIT), aflatrem (AT), secalonic acids (SA), cyclopiazonic acid (CPA), terrein (TR), sterigmatocystin (ST) and gliotoxin (GT), and other toxins produced by species of <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Aspergillus<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> plays a major role in food and human health. Mycotoxins exhibited wide range of toxicity to the humans and animal models even at nanomolar (nM) concentration. Consumption of detrimental mycotoxins adulterated foodstuffs affects human and animal health even trace amounts. Bioaerosols consisting of spores and hyphal fragments are active elicitors of bronchial irritation and allergy, and challenging to the public health. <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Aspergillus<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> is the furthermost predominant environmental contaminant unswervingly defile lives with a 40–90 % mortality risk in patients with conceded immunity. Genomics, proteomics, transcriptomics, and metabolomics approaches useful for mycotoxins’ detection which are expensive. Antibody based detection of toxins chemotypes may result in cross-reactivity and uncertainty. Aptamers (APT) are single stranded DNA (ssDNA/RNA), are specifically binds to the target molecules can be generated by systematic evolution of ligands through exponential enrichment (SELEX). APT are fast, sensitive, simple, in-expensive, and field-deployable rapid point of care (POC) detection of toxins, and a better alternative to antibodies.